PEMANFAATAN LIMBAH KULIT PISANG KEPOK (MUSA PARADISIACA LINN) DENGAN VARIASI BUAH NAGA MENJADI PERMEN FUNGSIONAL - Afriandi Afriandi; Lahming Lahming; Subari Yanto (Universitas Negeri Makassar, 2018)
This study aims to determine the effect of the concentration of dragon fruit juice addition to the manufacture of kapok banana pell candy and to know the acceptance of panelists on the candy produced. This research uses Completely Randomized Design (RAL) with the addition of dragon fruit juice. Parameters observed, moisture content, ash content, reducing sugar content, sucrose content, antioxidant levels, vitamin C levels with hedonic quality of color, texture, aroma, and taste. Based on the results of proximate test for water content, ash content, reducing s ugar content, sucrose content, antioxidant levels, and vitamin C content, the best result is the treatment with the addition of dragon fruit juice 300 gram with hedonic quality of color 6.92 , texture 6.9, aroma 6.59 and taste 7.35